2021
DOI: 10.1038/s41598-021-83268-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the composition of heterogeneous binder solutions by surface plasmon resonance biosensing

Abstract: Surface plasmon resonance-based biosensors have been extensively applied to the characterization of the binding kinetics between purified (bio)molecules, thanks to robust data analysis techniques. However, data analysis for solutions containing multiple interactants is still at its infancy. We here present two algorithms for (1) the reliable and accurate determination of the kinetic parameters of N interactants present at different ratios in N mixtures and (2) the estimation of the ratios of each interactant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Si Mehand et al [ 104 , 105 ] first demonstrated that it is possible to identify from the SPR recorded signal the kinetic parameters of two distinct analytes that are simultaneously injected over a given ligand. While the original intent of Si Mehand’s study was to increase the SPR biosensor throughput in a screening context, Gaudreault et al [ 106 ] recently extended this theoretical framework to the case of analytes. Here, the goal was to identify the kinetic parameters for each individual analyte within a complex analyte mixture, an asset if the analytes are difficult to separate from each other.…”
Section: Toward a Better Understanding Of The Igg-fcγr Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Si Mehand et al [ 104 , 105 ] first demonstrated that it is possible to identify from the SPR recorded signal the kinetic parameters of two distinct analytes that are simultaneously injected over a given ligand. While the original intent of Si Mehand’s study was to increase the SPR biosensor throughput in a screening context, Gaudreault et al [ 106 ] recently extended this theoretical framework to the case of analytes. Here, the goal was to identify the kinetic parameters for each individual analyte within a complex analyte mixture, an asset if the analytes are difficult to separate from each other.…”
Section: Toward a Better Understanding Of The Igg-fcγr Interactionmentioning
confidence: 99%
“…The model is described by the following ODE system, which can be integrated numerically: where represents the set of fractions of each analyte in the mixture. The basis of the fitting method used by Gaudreault et al [ 106 ] revolves around the fact that the model of Equation (7) exhibits the same behaviour at equilibrium as a 1:1 Langmuir model with the following parameters: …”
Section: Toward a Better Understanding Of The Igg-fcγr Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inadequate fit to an ideal 1:1 Langmuir model can typically be explained either by a poor SPR assay design or by the presence of a more complex interaction scheme. Such complexity can hail from the presence of heterogeneity in the system (either in the analyte [26,[28][29][30][31] or the ligand [85][86][87][88] molecules), the stoichiometry of the analyte-ligand interaction [89][90][91][92], or a conformational change following analyte-ligand binding [93,94]. Forest-Nault et al [51] provided a description of the modeling approaches that can be used to analyze such complexities in SPR data and offered insight on the modeling of IgG-Fcγ receptor (FcγR) interactions, which has long been studied using SPR and for which nonideal behaviors have repeatedly been observed and confirmed.…”
Section: Spr To Measure Kinetics and Affinitymentioning
confidence: 99%
“…Advances in the liquid handling and control systems have greatly improved the precision and sensitivity of SPR-based biosensors in the last three decades [15][16][17][18][19][20][21]. On top of this, robust protocols [22] and data analysis works [23][24][25][26][27][28][29][30][31] have helped establish SPR as a premiere technique in the field of biomolecule interaction analyses. Its main advantage lies in its ability to detect interactions without a label, which simplifies the assay design.…”
Section: Introductionmentioning
confidence: 99%